2019
DOI: 10.1016/j.jpedsurg.2018.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, severity and outcome of central line related complications in pediatric oncology patients; A single center study

Abstract: Background: Central venous access device (CVAD)-related complications are associated with high morbidity rates. This study was performed to underline the importance of CVAD-complication prevention and treatment. Methods: An audit of practice of CVAD-related complications in pediatric oncology patients receiving a CVAD between January 2015 and June 2017 was performed. CVADs included were totally implantable venous access ports (TIVAPs), Hickman-Broviac® (HB), nontunneled, and peripherally inserted CVADs. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 33 publications
8
49
0
Order By: Relevance
“…We found that both adverse events and dwell period complications are common in our patient cohort, with an overall incidence of 17.4% and 25.0% respectively. The incidence of adverse events observed during catheter implantation is consistent with the 4.5%-22.0% incidence reported in prior studies of pediatric oncology patients [12][13][14]. Although ultrasound guidance has been shown to reduce the incidence of failures and inadvertent arterial punctures in pediatric central venous catheterization [15], percutaneous landmark technique was predominantly utilized in our study as this approach is traditional at our…”
Section: Discussionsupporting
confidence: 86%
“…We found that both adverse events and dwell period complications are common in our patient cohort, with an overall incidence of 17.4% and 25.0% respectively. The incidence of adverse events observed during catheter implantation is consistent with the 4.5%-22.0% incidence reported in prior studies of pediatric oncology patients [12][13][14]. Although ultrasound guidance has been shown to reduce the incidence of failures and inadvertent arterial punctures in pediatric central venous catheterization [15], percutaneous landmark technique was predominantly utilized in our study as this approach is traditional at our…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3] CVC-related bloodstream infections often result in hospital admissions for the administration of intravenous antibiotics, postponement of treatment for primary disease, early CVC removal, or intensive care unit admissions due to severe sepsis. [4] Prevention of CVC-related bloodstream infections is therefore of the utmost importance. [5,6] The use of prophylactic antimicrobial lock solutions with or without the addition of an anticoagulant have been suggested as a method for the prevention of CVC-related bloodstream infections by preventing biofilm formation, killing bacteria and/or the inhibition of bacterial growth.…”
mentioning
confidence: 99%
“…Staphylococcus aureus was cultured in 27% (14/52) of catheter-related infections in our study. This prevalence is strikingly higher than the 5.2% of S. aureus cultured during central line-associated bloodstream infection (CLABSI) episodes in a report on CVAD-related complications in pediatric oncology patients from colleagues at our institution ( 33 ). In unpublished data by Van den Bosch et al on CVAD-related complications in neuroblastoma patients, significantly more S. aureus-CLABSIs and CLABSIs overall were observed in neuroblastoma patients receiving anti-GD2 immunotherapy.…”
Section: Discussionmentioning
confidence: 69%